2016
DOI: 10.1111/1756-185x.13008
|View full text |Cite
|
Sign up to set email alerts
|

Mean platelet volume as a marker for differentiating disease flare from infection in Behçet's disease

Abstract: MPV was significantly lower in patients with BD than controls. MPV declined in BD flare and increased in cases of infection in same patients. MPV may be useful as a marker of BD activity and its monitoring can be helpful for differentiating BD flare from infection in BD patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 45 publications
(49 reference statements)
0
5
1
Order By: Relevance
“…It has been reported that MPV is decreased in BD patients than in healthy control, regardless of clinical activity. 33‐36 In our study, although the MPV value showed no difference between RAS and control, it was significantly lower in patients with inactive BD compared with the other two groups. Although the cause of decreased MPV was not elucidated in studies, Jiang et al emphasised that MPV alone cannot be a suitable indicator of platelet activation since there is no clear correlation between platelet aggregation responses and platelet indexes 33,37 .…”
Section: Discussioncontrasting
confidence: 57%
See 2 more Smart Citations
“…It has been reported that MPV is decreased in BD patients than in healthy control, regardless of clinical activity. 33‐36 In our study, although the MPV value showed no difference between RAS and control, it was significantly lower in patients with inactive BD compared with the other two groups. Although the cause of decreased MPV was not elucidated in studies, Jiang et al emphasised that MPV alone cannot be a suitable indicator of platelet activation since there is no clear correlation between platelet aggregation responses and platelet indexes 33,37 .…”
Section: Discussioncontrasting
confidence: 57%
“…Also, non-identical technical factors such as blood sampling, and collection methods can also affect the MPV value. 36,57 These situations have been neglected in most of the studies. Whereas, firstly, we constituted three groups adjusted for possible confounders.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…80 Numerous studies found a negative correlation between MPV and autoimmune disease activity. 8183 In Behçet’s disease, for example, MPV decreased during disease exacerbation and rose during infection in same subjects. 81 These results emphasise the close interaction between thrombosis and inflammation by pointing to a relationship between low MPV values and chronic inflammation.…”
Section: Discussionmentioning
confidence: 98%
“…Differently, Ryu et al . [ 26 ] reported that MPV was significantly lower in patients with BD compared to controls and claimed that MPV may be useful as a marker of BD activity. According to the results of this study, MPV, PDW, and PCT levels were significantly higher in active and inactive ocular BD patients than controls.…”
Section: Discussionmentioning
confidence: 99%